Evolusi Gerakan Salafisme: Dari Masa Ibnu Taymiyyah Sampai Muhammad Bin Abdul Wahab - Nurfalina, Yuliana; Effendi, Effendi (Jurnal Kawakib, 2024)
Salafism, a reformist movement that follows a school of Islamic understanding unaffected by Hellenism. Its aim is to maintain the views of the salaf scholars. The author uses the historical method by collecting data through library research sourced from books, articles, and other related information. The results of this study discuss various Salafi schools that emphasize three main characteristics in their teachings, namely placing Islamic law (sharia) above reason, avoiding rationalist interpretations, and upholding the text of the Quran and Hadith. Of course, this is closely related to the influence of thinkers such as Ibn Taymiyyah who was the main thinker, followed by Muhammad bin Abdul Wahab as his successor